The Influence of Service Quality and Patient Satisfaction on Inpatient Loyalty in the Hospital Service Industry - Puspita, Mia; Paramata, Vip (PSPP JOURNALS, 2024)
Hospitals as a level of follow-up service after the health center must certainly have better services. Hospitals are a means to produce health degrees for community members. This study aims to analyze the influence of service quality and patient satisfaction on inpatient loyalty in the Hospital Service Industry. From the results of this literature review, the results of the journal above show that the quality of service in the form of tangible, reliability, responsiveness, assurance, and emphaty dimensions has a significant effect on patient satisfaction and loyalty. Service quality has a positive effect on patient satisfaction in providing health services. So that the higher the quality of service provided, the higher customer satisfaction will be. The latent variable of satisfaction has a positive relationship with loyalty, meaning that the higher the level of patient satisfaction, the greater the level of loyalty. According to researchers, in the future, hospitals must always provide good quality of service to all patients and always prioritize patient satisfaction so that patients will always visit or be loyal to the hospital.